The Pragmatist's Guide to Corporate Lean Strategy Incorporating Lean Startup and Lean Enterprise Practices in Your Business - Nir, Michael (Apress, 2018)
Use this practical, step-by-step guide on lean agile strategy to harness technological disruption at your large business to successfully advance your business rather than suffer a loss of business. The lean agile enterprise concept is demystified and translated into action as the author shares his experience with both success and major failure in areas such as healthcare, insurance, major airline, manufacturing, financial services, education, and big data. The author shares the good, the bad, and the ugly of enterprise-level adoption of lean startup practices (what we call a "lean corporation"). The book provides step-by-step instructions specifically targeted to technologists in multiple roles-from CEO to a developer on the ground-on how to build a "lean agile corporation" and avoid common traps. Building on the experience of the "lean startup" framework of Steven Blank and Eric Reis, this book takes these concepts to the enterprise level by providing tips and best practice guidelines, sharing "horror stories" and common anti-patterns in a fun and engaging way. What You'll Learn: Discover how you can contribute to your company as it becomes a lean agile corporation and survives technological and digital disruption Beat Facebook, Amazon, Apple, and Google at their own game by using methods they use to quickly experiment with new services and features Understand how to advance your career in a lean startup framework Know how you can trace your company's success to your daily work .